The impact of the catalyst layer structure on the performance of anion exchange membrane fuel cell. (20th December 2021) - Kim, Sungjun; Her, Min; Kim, Yongmin; Ahn, Chi-Yeong; Park, Sungbin; Cho, Yong-Hun; Sung, Yung-Eun
Highlights: The impact of electrode parameters for both electrodes on AEMFC performance was investigated individually. Commercial material-based AEMFC with high specific power over 3W mgPGM −1 with low PGM loading (0.2 mgPGM cm −2 ) was demonstrated. Abstract: Intrinsic water imbalance in AEMFC complicates the mass transport phenomena in the electrodes and causes performance loss. Because an AEMFC electrode is a complex multi-component system composed of agglomerates of carbon-supported catalyst bound to ionomer, balancing these components is critical for better water management. Herein, we clarify the influence of the three electrode parameters (ionomer content, active material loading, and active material to carbon ratio) on AEMFC performance using commercial AEM and AEI (FAA-3–50 membrane and FAA-3 ionomer) with standard precious metal catalysts (PtRu/C and Pt/C). The influence of the electrode parameters of each electrode (anode and cathode) was investigated individually. Physical and electrochemical measurements revealed that the cell performance was highly dependent on each electrode parameter for both electrodes, and it was confirmed that the supply of water by back-diffusion rather than oxygen at the cathode, as well as water flooding at the anode, limited the performance of the AEMFC. In particular, we demonstrate commercial material-based AEMFC with specific power over 3 W mgPGM −1 with low PGM loading (0.2 mgPGM cm −2 ) by adjusting the anode and cathode electrode parameters.